FORMULASI DAN EVALUASI MUTU FISIK SEDIAAN KRIM WAJAH DARI EKSTRAK KULIT BUAH DELIMA (Punica granatum L.) SEBAGAI ANTIACNE - Fitri, Aldesra; Wardana, Fendy (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Acne is one of the most common skin diseases, especially in teenagers because it can damage self-confidence. Acne is caused by inflammation by pilosebaseae molecules characterized by the presence of nodules, papules, blackheads, and pustules. One alternative that can be used as a treatment using herbs is with red pomegranate peel (Punica granatum L.). Pomegranate peel contains quercetin compounds contained in flavonoids, tannins, alkaloids, and terpenoids. This study was conducted to determine the physical quality and the effect of variations in the concentration of Triethanolamine (TEA) as an emulgator in face cream preparations. This research uses experimental methods to obtain research data. Anti-acne cream preparations from pomegranate peel extract were made with TEA concentrations of 2%, 3% and 4%. The results of pomegranate peel extract cream preparation meet the requirements of organoleptical physical quality test, homogeneity, pH, adhesion, spreadability and viscosity. Statistical test results show that the variation of TEA affects the physical quality of spreadability with a sig value (p=<0.05). Statistical test results showed that the variation of TEA had no effect on the physical quality of spreadability with a sig value (p => 0.05). Formulation 3 with 4% TEA concentration produced the most intense color preparation.